Structure formation and multistep nucleation in Casting Al-Mg-Si alloys - Trudonoshyn, Oleksandr; Prach, Olena; Slyudova, Anna; Lisovskii, Vitaliy (International Journal of Cast Metals Research, 2020)
The process of multistep nucleation during solidification in hypoeutectic Al-Mg-Si casting alloys was investigated. The morphology of the nucleating particles, Mg2Si primary crystals and Al-Mg2Si eutectic, was investigated with scanning electron microscopy (SEM) on polished and deep etched microsections. The mechanism of formation of the Mg2Si crystal was attributed to heterogeneous nucleation on the nucleating particles. It was observed that the majority of the alloys particles found in the studied are oxides. It was established that eutectic Al–Mg2Si in hypoeutectic alloys has the morphology of ‘eutectic crystal’, where one face of the crystal has triangular-spiral morphology. The mechanism of formation of Al-Mg2Si eutectic cells is attributed to epitaxial growth on Mg2Si crystals. The microhardness of the structural components (Mg2Si crystals, α-Al dendrites, Al-Mg2Si eutectic, and Al3Ti crystals) was measured using Vickers hardness tester.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Al-alloys; heterogeneous nucleation; multistep nucleation; nucleating particles; primary crystals; spiral eutectic